Implementation of al-wadiah (saving instrument) contract in contemporary gold transactions - Shuib, Mohd Sollehudin; Md Hussain, Muhammad Nasri; Osman, Amirul Faiz; Hashim, Hydzulkifli; Fadzil, Aiman (Ideal True Scholar, 2016)
This study focused on how wadiah (safekeeping or saving instrument) applied in contemporary gold transaction.The aims of this article is to substantiate the concepts of wadiah in contemporary gold trading based on the main sources of Islamic law of contract.Contemporary gold trading is like other retails and online trading.However, according to Islamic business contract, gold is categorized under a special law of transaction items and it must follows a specific law of Islamic business transaction. The legality of the wadiah concepts is utmost important to be verified before its implementation. This study was designed as qualitative stle of method in explore wadiah concept, legality and how wadiah implemented in gold transaction.The finding shows that the wadiah concept is permissible in Islam. Furthermore, the wadiah also play important role in contemporary gold trading.(Significant) Hence, wadiah contract can helps to resolve the gold trading issues where the physical assets of gold are distance from the buyer.